Plan de negocios para la creación de una empresa recicladora de plástico PET, en el distrito especial de Buenaventura (2016)
The subject of research is a study on solid waste management, where the problem lies in the little recycling that makes this product, and according to population growth only 9.31% is recycled. Therefore it is proposed to develop a business plan for the creation of a PET plastic recycling company, determine market characteristics, investigating and determining existing regulations about companies whose corporate purpose and establish recycling amounts investment needed for assembly of a business processing plastic waste It was established with the study that recycling is a lucrative activity of two major connotations by one party contributes to the strengthening of a culture of social and environmental responsibility with the environment and other resource generation to improve conditions of life of those incursions in this type of business. The project is an alternative to environmentally recycling process and the search for solutions to reduce the quantities of materials such as paper and cardboard existing city. As for the market study can conclude that we are facing a dynamic market for the purchase basically novelty products and hygienic ideals. In terms of marketing it can be concluded that it is a growing market demanding a marked trend towards quality and proper handling of the product. Administratively, it is necessary to create a name that adheres to the policies of his creation, which in this case must be limited company. The technical study concludes that it is necessary the company's geographical expansion. The project in question is profitable since its IRR is 15% which is above the cost of capital employed, the ratio B / C is $ 1.42 allowing profit of $ 0.87 for every dollar invested, and the NPV is $ 16,633,925 more than zero becoming an attractive prospect for investors.